Diagnostic Genesis Features of Au-Ag Selenide-Telluride Mineralization of Western Java Deposits - Euis Tintin Yuningsih; Hiroharu Matsueda; Mega F. Rosana (Indonesian Journal on Geoscience, 2016)
DOI: 10.17014/ijog.3.1.67-76The ore mineralogy of the westernmost part of West Java such as Pongkor, Cibaliung, Cikidang, Cikotok, and Cirotan are characterized by the dominance of silver-arsenic-antimony sulfosalt with silver selenides and rarely tellurides over the argentite, whereas the eastern part of West Java including Arinem and Cineam deposits are dominated by silver-gold tellurides. Mineralogy of Se-type deposits at Pongkor, Cikidang, Cibaliung, Cisungsang, and Cirotan and Te-type deposits at Arinem and Cineam shows their different geochemical characteristics. Mineralogical and geochemical differences can be explained by variation of physico-chemical conditions that existed during gold-silver deposition by applying the phase relation among sulfide, telluride, and selenide mineral association in the deposits. The relative values of ƒSe2(g), ƒTe(g), and ƒS2(g) control the actual presence of selenide or telluride minerals within the West Java deposits, which also depend on their concentrations in the hydrothermal fluid. Even though the concentration of selenium in the hydrothermal fluid of Te-type deposits might have been similar or even higher than that in the Se-type, early substitution of selenium in the sulfide minerals prevents its concentration in the hydrothermal fluid to the levels for precipitating selenide minerals. Therefore, early sulfide mineral deposition from reduction fluids will not increase the ƒSe2(g)/ƒS2(g) ratio to form selenide minerals in Te-type deposits of Arinem and Cineam, other than selenium-bearing sulfide mineral such as Se-bearing galena or Se-bearing pyrargyrite-proustite.